Pengaruh Brand Image dan Harga Terhadap Minat Beli Mobil Listrik Melalui Gaya Hidup Sebagai Variabel Intervening Di Area Kota Malang Jawa Timur - Andre Martinus; Fathorrahman; Pradiani, Theresia (Jurnal Ilmiah Administrasi Bisnis dan Inovasi, 2023)
Electric cars powered by batteries have 100% minimal pollutants. Basically, although power plants that produce electricity can emit pollutants, electricity from nuclear, hydro, solar or wind power plants produces less air pollution. The performance benefits of electric cars provide quiet operation and stronger acceleration, as well as requiring less maintenance than internal combustion engines, and reduced energy dependence, as electricity is the source of household energy. The quantitative approach is a method as a solution to solving problems that occur, where the research population is all electric car users in Malang City. The sampling technique used was purposive sampling so that 100 respondents were obtained who would later fill out the research questionnaire. This research is also supported by data collection techniques through literature study and field research to strengthen the research results. Data analysis in this study used descriptive analysis, classical assumption tests and regression tests which were then continued with the Sobel test. Data were processed statistically with the SPSS program. The results show that 38% of lifestyle is influenced by brand image, 52.6% of lifestyle is influenced by price, 44.6% of purchase intention is influenced by brand image, purchase intention is not influenced by price, 62.4% of purchase intention is influenced by brand image through lifestyle, and 12.8% of buying interest is influenced by price through lifestyle.